MiR-204 in Acute Myeloid Leukemia: A Comprehensive Review - Oum Kaltoum, Ait Boujmia (Asian Pacific Journal of Cancer Nursing, 2026)
Acute myeloid leukemia (AML) is the most lethal of all leukemias, which is caused by genetic aberrations such as abnormal miRNA expression profiles. MicroRNA-204 is a small RNA that plays crucial physiological roles in retinal development and adipogenesis. In addition it can also impact tumor initiation, growth, and progression by regulating different processes. In AML, many studies have shown that miR204 can be considered a diagnosis and prognosis biomarker that can improve differentiation, apoptosis, survival, and response to chemotherapy by inhibiting different targets. The available, current knowledge concerning the influence of microRNA 204 on AML is summarized in this short review. Understanding the mechanism of action of miR-204 in AML could help treat and establish effective therapies.